Effective conservation planning requires learning and adaptation. Issue 8 (8th September 2009) - Grantham, Hedley S; Bode, Michael; McDonald-Madden, Eve; Game, Edward T; Knight, Andrew T; Possingham, Hugh P
Abstract : Conservation decisions often involve uncertainty about the underlying ecological and social systems and, in particular, how these systems will respond to the implementation of conservation actions. Future decision making can be improved by learning more about these systems and their responses to past conservation actions, by evaluating the performance of the actions being undertaken. This is a "passive" adaptive management approach to conservation. However, the purposeful and experimental application of different conservation actions can yield greater knowledge through more rapid and targeted learning. This is an "active" adaptive management approach to conservation. Improving future management decisions through learning should be viewed as essential to all conservation plans. Unfortunately, the incorporation of explicit learning processes within the greater framework of conservation planning processes is rare. Here, we provide an overview of factors to consider when attempting the implementation of an adaptive approach to conservation planning, along with ideas for future research.